2017
DOI: 10.1007/s10389-017-0841-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in profile of patients seeking alcohol treatment and treatment outcomes following policy changes

Abstract: AimIn 2007, the legal obligation to deliver alcohol treatment to the public was transferred to the 98 municipalities of Denmark. This resulted in changes in how alcohol treatment centers in Denmark work. The aim of the present study was to describe the patient profiles and treatment outcomes in the alcohol treatment centers regarding regional variation and changes over time.Subjects and methodsThis is a descriptive, register-based study of patients enrolled in alcohol treatment centers from 2006–2014 in Denmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…Most individuals with AUD are offered outpatient treatment when seeking treatment in Denmark. The public outpatient treatment is paid via taxes and is open for self-referral, and patients can remain anonymous during treatment [35]. Only alcohol problems are treated at the outpatient clinic; individuals with mainly illegal drug abuse are treated elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Most individuals with AUD are offered outpatient treatment when seeking treatment in Denmark. The public outpatient treatment is paid via taxes and is open for self-referral, and patients can remain anonymous during treatment [35]. Only alcohol problems are treated at the outpatient clinic; individuals with mainly illegal drug abuse are treated elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol use disorder (AUD) is a preventable and treatable disorder, yet the prevalence of alcohol dependency and hazardous use is high in the Danish population [1]. Moreover, it is estimated that only 10 % of alcohol-dependent individuals receive treatment [2], even though treatment is publicly financed and free at the point of use. Further, treatment of AUD is associated with a range of compliance factors, which means that even when an individual enters the treatment facility, his/her risk of treatment interruption and relapse remains high [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that the impact of excessive and dependent alcohol use is massive, both on the individual and on society (WHO 2014). Premature dropout and lack of success from treatment for alcohol use disorder is, however, not uncommon (Schwarz et al 2018), and it has been difficult to identify a particular and single treatment approach that secures high level of treatment successes for all persons seeking treatment for alcohol use disorders (AUD). It has been suggested that the reason for this is that persons with AUD are heterogeneous in many aspects, and vary in terms of social background, gender, age, intelligence, mood, attitude to their alcohol use, social support, the severity of their drinking problem, and a wide range of other individual characteristics (Burnam and Watkins 2006).…”
Section: Introductionmentioning
confidence: 99%